(untitled) (Práxis Educativa, 2024)
This article presents the main results of a comparative study on the associative and participatory reality in Porto (Portugal), before and after the pandemic. It is a longitudinal qualitative research that began in 2018, analysing the sociocommunity work of five entities. In 2022, the second phase was conducted with the aim of understanding to what extent the pandemic could motivate changes in their associative dynamics. Semi-structured interviews were conducted with key informants, and the information was analysed based on topics. The main conclusions point to an urgent need for adaptation, which continues in this new social scenario. The most significant changes affect the work methodology, and the major difficulties are economic, as well as a reduction in human resources. Benefits derived from the pandemic are also recognized, such as new opportunities linked to internet use and an increase in participation. Keywords: Participation. Association. Pandemic.